Engineering Bamboo Leaves Into 3D Macroporous Si@C Composites for Stable Lithium-Ion Battery Anodes - Wu, Hao; Jiang, Yingying; Liu, Wenjun; Wen, Hong; Dong, Shihui; Chen, Huan; Su, Liwei; Wang, Lianbang (Frontiers in Chemistry, 2022)
Silicon is considered as the most promising candidate for anodes of next generation lithium-ion batteries owing to its natural abundance and low Li-uptake potential. Building a macroporous structure would alleviate the volume variation and particle fracture of silicon anodes during cycling. However, the common approaches to fabricate macroporous silicon are complex, costly, and high energy-consuming. Herein, bamboo leaves are used as a sustainable and abundant resource to produce macroporous silicon via a scalable magnesiothermic reduction method. The obtained silicon inherits the natural interconnected network from the BLs and the mesopores from the BL-derived silica are engineered into macropores by selective etching after magnesiothermic reduction. These unique structural advantages lead to superior electrochemical performance with efficient electron/ion transport and cycling stability. The macroporous Si@C composite anodes deliver a high capacity of 1,247.7 mAh g−1 after 500 cycles at a current density of 1.0 A g−1 with a remarkable capacity retention of 98.8% and average Coulombic efficiency as high as 99.52% for the same cycle period. Furthermore, the rate capabilities of the Si@C composites are enhanced by conformal carbon coating, which enables the anode to deliver a capacity of 538.2 mAh g−1 at a high current density of 4.0 A g−1 after 1,000 deep cycles. Morphology characterization verifies the structural integrity of the macroporous Si@C composite anodes. This work demonstrated herein provides a simple, economical, and scalable route for the industrial production of macroporous Si anode materials utilizing BLs as a sustainable source for high-performance LIBs.